Post-marathon decline in right ventricular radial motion component among amateur sportsmen. (14th October 2021) - Lewicka-Potocka, Z; Dabrowska-Kugacka, A; Lewicka, E; Kaleta-Duss, A M; Danilowicz-Szymanowicz, L; Kubik, M; Faran, A; Szymeczko, P; Galaska, R; Fijalkowski, M; Raczak, G
Abstract: Introduction: Running the marathon may be followed by post-exercise "cardiac fatigue" manifesting as transient right ventricular (RV) systolic and diastolic impairment. It is the thin-walled RV that is predominantly affected by the exercise-induced overload, with little if any, impact on the left ventricle (LV) [1]. The 2-D echocardiographic (ECHO) assessment of RV is challenging and may be incomplete since conventional measures reflect only the longitudinal motion (displacement of tricuspid annulus towards the apex) [2]. The mechanics of RV can be separated into two more components, anteroposterior (stretching RV wall by contracting septum) and radial (internal relocation of the RV free wall) [2]. The significance and relative contribution of motion components to global RV function may not be equal, and their interplay can vary depending on concomitant diseases [3]. Purpose: We aimed to analyse the pathophysiology of RV exhaustion associated with a marathon run with 3-D ECHO, which allows precise estimation of all RV motion components and their contribution to RV global function. Methods: The study included 34 healthy males (mean age of 40±8 years), amateurs, who finished the marathon in northern Poland. The 3-D ECHO was performed 2 weeks before (stage I), at the marathon finish line (stage II) and 2 weeks after the competition (stage III). According to the ReVISION method (Right ventricular separate wall motion quantification) the global RV function was decomposed to longitudinal (L_), anteroposterior (AP_) and radial (R_) [3]. By dividing componential ejection fractions (EF) with global RV EF, L_EFi, AP_EFi, and R_EFi ratios were obtained. Results: When comparing results from stage I and III there were no significant differences (Table 1). The analysis revealed post-run decline in RV EF with no changes in LV EF. The quantification of the RV motion components showed reduction in R_EF after the marathon with no changes in AP_EF or L_EF. The relative contribution of componential EF to global RV function were permanent and was not influenced by the competition. Conclusions: Marathon run resulted in transient RV dysfunction arising from decline in radial shortening. Noteworthy, the componential interplay between wall motion compartments was preserved in pre- and post-run assessment. The ReVISION method enables the comprehensive analysis of the competing RV. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): The study was supported by the project POWR.03.05.00-00-z082/18 co-financed by the European Union through the European Social Fund under the Operational Programme Knowledge Education Development 2014–2020